SOCIAL PRACTICES IN WATER USE DRIVE VULNERABILITY IN FOREST EDGE VILLAGE COMMUNITIES IN SUMEDANG REGENCY - Yunita, Desi; Nurwati, Nunung; Gunawan, Wahyu; Azman, Azlina (Universitas Padjadjaran, 2024)
This research focuses on social practices of water resource use in forest fringe communities. The existence of human water needs interacts with and forms patterns of relationships, with human water forming social institutions and social institutions, and the existence of social practices that abundant water encourages social change in communities facing scarcity. Old knowledge that is maintained and the assumption that water will never run out is seen in water use habits and ignoring water conservation practices. Potentially causing water vulnerability, especially in families working as farmers and families who do not have water reservoirs. The theory used looks at the social practices of Antony Giddens. The qualitative approach with the PRA method, with observation, interview, mapping, and FGD techniques, helps map practices in water use, and then the qualitative analysis is carried out. The results of this study show that there are water groups in hamlet areas that maintain old management practices, where group members who contribute early to finding springs have “patent” rights to obtain water while living in the area. However, this right has yet to adapt to changes in physical environmental conditions, such as reduced forest land cover and changes in the social environment where the village population continues to grow. While the rules made by the “patent” group give dominance to members materially, therefore individual practice still views that abundant water will not run out, so water use tends to be wasteful. Then, the practice of agents perpetuates or maintains a habit, which means that not much effort has been made by the community to carry out preventive practices to protect water resources, as seen from the Competence, namely knowledge and skills of water use are still simple and do not have the Competence to prevent vulnerability risks caused by the water crisis. So, it has the potential to face vulnerability, especially in families that do not have large-capacity shelters and farmer groups that rely on agricultural products. Agents as transformative actors, their practices passive, recursive, and discursive practices continue to be reproduced, maintaining old patterns.